Essays on the macroeconomic impact of financial openness - O'Donnell, Barry (Trinity College (Dublin, Ireland). Department of Economics, 2003)
This thesis uses new data to examine the impact of a quantitative measure of international financial integration on various indicators of macroeconomic performance. Proponents of greater openness to financial flows maintain th at more rapid economic development is an inevitable consequence of such an experience. In contrast, skeptics argue that any potential benefits of increasing financial openness are outweighed by the costs associated with greater economic instability and vulnerability caused by volatile capital flows. In general, the results presented in this thesis provide reasonably strong support for the view that greater financial openness hinders macroeconomic performance in developing countries.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin